Dividend Policy Study Reviewed from Liquidity and Debt Ratio: Signaling Theory Perspective in Indonesia - Putu Diah ASRIDA; I Gede Agus Adi SAPUTRA; Bayu PASUPATI (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study aims to analyze dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) by reviewing the effect of liquidity and debt ratios through the perspective of signaling theory. Using liquidity ratio proxied by Current Ratio (CR) and debt ratio measured by Debt to Equity Ratio (DER), the results showed that liquidity has a significant negative effect on dividend policy, with a significance value of 0.000 and beta -2.933. This indicates that the higher the liquidity, the lower the dividend policy applied by the company. On the other hand, the debt ratio has a significant positive effect on dividend policy, with a significance value of 0.000 and beta 0.729, which indicates that the higher the company's leverage, the greater the dividend policy distributed. This finding supports the signaling theory perspective, where companies use dividend policy to signal to investors about the company's financial condition and stability. This study suggests that firms consider the balance between liquidity, debt structure, and dividend policy, and pay attention to how these decisions can affect market perceptions and relationships with investors.